Resolving the paradox of conflicting glacial chronologies: Reconstructing the pattern of deglaciation of the Magellan cordilleran ice dome (53–54°S) during the last glacial – interglacial transition - Robert D. McCulloch; Michael J. Bentley; Derek Fabel; Hans Fernández-Navarro; Juan-Luis García; Andrew S. Hein; Carla Huynh; Stewart S.R. Jamieson; María-Paz Lira; Christopher Lüthgens; Grace A. Nield; Manuel San Román; et al. (Quaternary Science Reviews, 2024)

Local Wind Regime Induced by Giant Linear Dunes: Comparison of ERA5-Land Reanalysis with Surface Measurements - Cyril Gadal; Pauline Delorme; Clément Narteau; Giles F. S. Wiggs; Matthew Baddock; Joanna M. Nield; Philippe Claudin (Boundary-Layer Meteorology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The gene cassette metagenome is a basic resource for bacterial genome evolution - Andrew J. Holmes; Michael R. Gillings; Blair S. Nield; Bridget C. Mabbutt; K. M. Helena Nevalainen; H. W. Stokes (Environmental Microbiology, 2003)
Summary Lateral gene transfer has been proposed as a fundamental process underlying bacterial diversity. Transposons, plasmids and phage are widespread and have been shown to significantly contribute to lateral gene transfer. However, the processes by which disparate genes are assembled and integrated into the host regulatory network to yield new phenotypes are poorly known. Recent discoveries about the integron/gene cassette system indicate it has the potential to play a role in this process. Gene cassettes are small mobile elements typically consisting of a promoterless orf and a recombination site. Integrons are capable of acquisition and re‐arrangement of gene cassettes and of the expression of their associated genes. The potential of the integron/gene cassette system is thus largely determined by the diversity contained within the cassette pool and the rate at which integrons sample this pool. We show here using a polymerase chain reaction (PCR) approach by which the environmental gene cassette (EGC) metagenome can be directly sampled that this metagenome contains both protein‐coding and non‐protein coding genes. Environmental gene cassette‐associated recombination sites showed greater diversity than previously seen in integron arrays. Class 1 integrons were shown to be capable of accessing this gene pool through tests of recombinational activity with a representative range of EGCs. We propose that gene cassettes represent a vast, prepackaged genetic resource that could be thought of as a metagenomic template for bacterial evolution.